2011
DOI: 10.12693/aphyspola.120.16
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of Swift Proton Transmission through Tapered Glass Capillaries

Abstract: A study of the 150-300 keV proton beam transmission through glass (borosilicate) tapered capillaries with different diameters of the input and output of the capillary was performed. The focusing effect was observed. The areal density of the transmitted beam is enhanced by approximately 20 times. It was shown that changing a taper angle from 0.5 deg to 1.7 deg evidences the increase of the transmission coefficient more than by 300 times keeping the initial energy spectrum of ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…2 Should alternate lines of research to those suggested for use prove more advantageous, then they may be substituted. [16,17,22]. After this self-organized charge-up of the inner wall has occured, the limiting factor can become that of the outlet diameter of the tapered capillary, the smallest of which so far recorded is 80 nm [16].…”
Section: Current Technology/researchmentioning
confidence: 97%
See 2 more Smart Citations
“…2 Should alternate lines of research to those suggested for use prove more advantageous, then they may be substituted. [16,17,22]. After this self-organized charge-up of the inner wall has occured, the limiting factor can become that of the outlet diameter of the tapered capillary, the smallest of which so far recorded is 80 nm [16].…”
Section: Current Technology/researchmentioning
confidence: 97%
“…Standard focusing methods using magnets are not accurate enough on their own, and the muon-magnetic-microscope [20] is being developed with positive muons in mind. While it may also yield techniques relevant to the focusing of l À , this is not investigated further, as a method utilizing capillary optics [16][17][18][19]22] should suffice. This method has been tested on an array of beams including various slow highly charged ions (HCIs), MeV ions, positive and negative muons, electrons, positrons and protons [16][17][18][19]22].…”
Section: Current Technology/researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Thompson (1997) showed the presence of pores changes the energy loss during the transition of particles through the sample but allows to appear a guiding effect by the required pore configuration. In (Komarov et al 2011) considered the transition of a proton beam with energy from 150 to 320 keV through tapered glass capillaries. Was shown that when beam passes through capillary, the angular width of the initial beam remains almost unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Manzoor S. et al [30] showed that pores could affect energy loss during the transition of particles through the sample but, at the same time, a guiding effect could appear in the required pore configuration. In [31], the transition of a proton beam with energy from 150 to 320 keV through tapered glass capillaries was considered. As it was presented, when the beam passes through capillaries, the angular width of the initial beam remains almost unchanged.…”
Section: Introductionmentioning
confidence: 99%